Danoprevir, an HCV NS3/4A protease inhibitor, improves insulin sensitivity in patients with genotype 1 chronic hepatitis C. Issue 12 (21st September 2010) - Moucari, Rami; Forestier, Nicole; Larrey, Dominique; Guyader, Dominique; Couzigou, Patrice; Benhamou, Yves; Voitot, Hélène; Vidaud, Michel; Seiwert, Scott; Bradford, Bill; Zeuzem, Stefan; Marcellin, Patrick
Abstract : Background/aim: Insulin resistance (IR) is a major predictor of treatment failure in patients with hepatitis C virus (HCV) infection treated with peginterferon/ribavirin. The aim of this study was to evaluate the short-term effect of an HCV protease inhibitor monotherapy on IR in parallel with an antiviral effect. Patients/methods: In a phase 1b placebo-controlled study, four cohorts of treatment-naïve patients with genotype 1 HCV received danoprevir (ITMN-191/RG7227), a protease inhibitor, or placebo (8/2 patients in each cohort respectively) in a gelatin capsule every 12 h (100, 200 mg) or 8 h (100, 200 mg) for 14 days. A fifth cohort including prior non-responders to peginterferon/ribavirin was similarly randomised to receive placebo or 300 mg danoprevir every 12 h. IR was assessed with the homeostasis model (HOMA-IR) at baseline and days 7, 14 and 15. Results: Serum HCV-RNA and HOMA-IR correlated significantly (Spearman rho=0.379, p<0.0001). At baseline, mean±SD serum HCV-RNA level and mean±SD HOMA-IR score were 6.2±0.5 log10 IU/ml and 3.8±1.9, respectively. At the end of 14 days of monotherapy the mean±SD decrease in viral load was 2.2±1.3 log10 IU/ml (p<0.0001) in patients who received the active drug (n=40). In parallel, the mean±SD HOMA-IR score also decreased in these patients by 1.6±1.1 (p<0.0001), with a close correlation between the extent of HOMA-IR improvement and the decrease in viral load. By contrast, serum HCV-RNA and HOMA-IR remained unchanged in patients who received placebo (n=10; 6.3±0.5 log10 IU/ml and 3.8±2.5, respectively). Conclusion: HCV protease inhibitor may restore insulin sensitivity in patients with genotype 1 HCV. The place of insulin sensitisers remains to be determined in the era of triple therapy.